Adaptive Real-Time Characterisation of Composite Precursors in Manufacturing - Koptelov, Anatoly; Belnoue, Jonathan P-H.; Georgilas, Ioannis; Hallett, Stephen R.; Ivanov, Dmitry S. (Frontiers in Materials, 2022)
This paper explores the application of a novel adaptive consolidation sensor framework for the characterisation of composite precursors. The designed framework develops material-driven test programmes in real-time and defines robust material models for the studied composite precursor. The proposed approach allows to remove any subjective judgement about the material behaviour and to reduce human involvement at the experimentation stage. The proposed framework along with the developed data transfer hardware setup was put to the test within several characterisation exercises. Two different material systems were tested. The output of the proposed testing method – model and properties for the tested materials – is compared with the results of the conventional deterministic characterisation tests.